Network: Theorizing knowledge work in telecommunications - Spinuzzi, Clay (Cambridge University Press, 2013)
How does a telecommunications company function when its right hand often doesn’t know what its left hand is doing? How do rapidly expanding, interdisciplinary organizations hold together and perform their knowledge work? In this book, Clay Spinuzzi draws on two warring theories of work activity – activity theory and actor–network theory – to examine the networks of activity that make a telecommunications company work and thrive. In doing so, Spinuzzi calls a truce between the two theories, bringing them to the negotiating table to parley about work. Specifically, about net work: the work that connects, coordinates, and stabilizes polycontextual work activities.